ANALISIS PERBANDINGAN AVERAGE ABNORMAL RETURN DAN AVERAGE TRADING VOLUME ACTIVITY SEBELUM DAN SETELAH PEMILIHAN LEGISLATIF DAN PEMILIHAN PRESIDEN TAHUN 2019 - Muhajir Muhajir; Nita Erika Ariani (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2019)
This study aims to analyzed the diffirences in average abnormal pengmbalians and average trade volume activity before and after the 2019 legislative and presidential election.The result shows that: (1) Base on the results of the test of the average abnormal pengmbalian while the event periode, the average abnormal pengmbalian before and after the 2019 legislative and presidential election. (2) From the results of the test of the average trading volume activity before and after 2019 legislative and presidential election es shows that there are statistically different average trading volume activity before and after 2019 legislative and presidential election. Based on the results, the issuers are advisable to improve the fundamental quality of the company. Investors are recommended to improve their competence in interpreting information related to stock prices as good news or bad news. For further research, it is recommended to expand research sample and the observation period